2018
DOI: 10.1186/s12870-018-1267-8
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a male-fertility restoration locus for the A4 cytoplasmic-genic male-sterility system in pearl millet using a genotyping-by-sequencing-based linkage map

Abstract: BackgroundPearl millet (Pennisetum glaucum (L.) R. Br., syn. Cenchrus americanus (L.) R. Br) is an important cereal and fodder crop in hot and arid environments. There is great potential to improve pearl millet production through hybrid breeding. Cytoplasmic male sterility (CMS) and the corresponding nuclear fertility restoration / sterility maintenance genes (Rfs) are essential tools for economic hybrid seed production in pearl millet. Mapping the Rf genes of the A4 CMS system in pearl millet would enable mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…The A 4 male-fertility restoration genes are most likely dominantly monogenically inherited, according to Gupta et al (2012) and phenotypic data from Pucher et al (2018). However, the same study of Pucher et al (2018) identified major fertility restoration and maintenance QTLs for pollen production and selfed seed set, which explained only 14.5 and 9.9% of the phenotypic variance, respectively. This led to the conclusion that minor or modifying genes are also present.…”
Section: Requirements For Commercial Hybrid Seed Production: the Cytomentioning
confidence: 99%
See 4 more Smart Citations
“…The A 4 male-fertility restoration genes are most likely dominantly monogenically inherited, according to Gupta et al (2012) and phenotypic data from Pucher et al (2018). However, the same study of Pucher et al (2018) identified major fertility restoration and maintenance QTLs for pollen production and selfed seed set, which explained only 14.5 and 9.9% of the phenotypic variance, respectively. This led to the conclusion that minor or modifying genes are also present.…”
Section: Requirements For Commercial Hybrid Seed Production: the Cytomentioning
confidence: 99%
“…However, screening of OPVs for fertility restoration ability is challenging and still incomplete (Rai, Kulkarni, Thakur, Haussmann, & Mgonja, 2006). More recently published research suggests screening WA germplasm for A 4 male-fertility restoration genes or transferring them via backcrossing into WA-adapted material with pure phenotypic or better marker-assisted selection (Gupta, Rai, Govindaraj, & Rao, 2012;Pucher et al, 2018). The A 4 male-fertility restoration genes are most likely dominantly monogenically inherited, according to Gupta et al (2012) and phenotypic data from Pucher et al (2018).…”
Section: Requirements For Commercial Hybrid Seed Production: the Cytomentioning
confidence: 99%
See 3 more Smart Citations